Regulation of synaptic function and lipid metabolism - Tongtong Zhang; Yunsi Yin; Xinyi Xia; Xinwei Que; Xueyu Liu; Guodong Zhao; Jiahao Chen; Qiuyue Chen; Zhiqing Xu; Yi Tang; Qi Qin (Neural Regeneration Research)
Synapses are key structures involved in transmitting information in the nervous system, and their functions rely on the regulation of various lipids. Lipids play important roles in synapse formation, neurotransmitter release, and signal transmission, and dysregulation of lipid metabolism is closely associated with various neurodegenerative diseases. The complex roles of lipids in synaptic function and neurological diseases have recently garnered increasing attention, but their specific mechanisms remain to be fully understood. This review aims to explore how lipids regulate synaptic activity in the central nervous system, focusing on their roles in synapse formation, neurotransmitter release, and signal transmission. Additionally, it discusses the mechanisms by which glial cells modulate synaptic function through lipid regulation. This review shows that within the central nervous system, lipids are essential components of the cell membrane bilayer, playing critical roles in synaptic structure and function. They regulate presynaptic vesicular trafficking, postsynaptic signaling pathways, and glial–neuronal interactions. Cholesterol maintains membrane fluidity and promotes the formation of lipid rafts. Glycerophospholipids contribute to the structural integrity of synaptic membranes and are involved in the release of synaptic vesicles. Sphingolipids interact with synaptic receptors through various mechanisms to regulate their activity and are also involved in cellular processes such as inflammation and apoptosis. Fatty acids are vital for energy metabolism and the synthesis of signaling molecules. Abnormalities in lipid metabolism may lead to impairments in synaptic function, affecting information transmission between neurons and the overall health of the nervous system. Therapeutic strategies targeting lipid metabolism, particularly through cholesterol modulation, show promise for treating these conditions. In neurodegenerative diseases such as Alzheimer’s disease, Parkinson disease, and amyotrophic lateral sclerosis, dysregulation of lipid metabolism is closely linked to synaptic dysfunction. Therefore, lipids are not only key molecules in neural regeneration and synaptic repair but may also contribute to neurodegenerative pathology when metabolic dysregulation occurs. Further research is needed to elucidate the specific mechanisms linking lipid metabolism to synaptic dysfunction and to develop targeted lipid therapies for neurological diseases.